PENGARUH MODAL DAN BIAYA PRODUKSI TERHADAP PENDAPATAN BISNIS PERTANIAN KARET (STUDI PADA PERTANIAN KARET DESA KADUR, RUPAT UTARA, BENGKALIS) - Siti Suhaiza; Ruzikna " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This study aims to determine the capital and production costs as well as the income of rubber farmers in Kadur Village, Rupat Utara District, Bengkalis Regency and the effect of capital and production costs on the income of rubber farmers in Kadur Village, North Rupat District, Bengkalis Regency. The type of Research used in this research ia quantitative research. Data were collected using a questionnaire method and then analyzed descriptively and inferentially. The results showed that capital and production costs had an effect on the income of rubber farmers in Kadur Village, Rupat Utara District, Bengkalis Regency. The partial test value of capital was 1,965 with a significant level of 0.072 and production costs of 2,332 with a significant level of 0.003. Based on the simultaneous test, capital and production costs together have an effect on income with a value of 47,192 with a significant level of 0.068. Keywords : Capital, Production cost, Income